Frequency of Social Media and Digital Scholarship Keywords in U.S. Medical Schools' Promotion and Tenure Guidelines. (January 2022) - Maldonado, Graciela; Smart, Jonathan; Wiechmann, Warren; Kaplan, Sherrie H.; Billimek, John; Wray, Alisa; Toohey, Shannon; Boysen-Osborn, Megan
Abstract : Purpose: Medical schools must have clear policies and procedures for promotion and tenure (P&T) of faculty. Social media and digital scholarship (SMDS) is an emerging form of scholarship capable of reaching audiences quickly, conveniently, and in a wide variety of formats. It is unclear how frequently SMDS is considered during P&T reviews. The authors sought to determine whether current P&T guidelines at medical schools consider SMDS. Method: The authors acquired P&T guidelines from any U.S. Liaison Committee on Medical Education–accredited medical school (or their governing university) that were available online between October and December 2020. Using an iterative process, they developed a bank of keywords that were specific to SMDS or that could include SMDS between October and December 2020. The authors searched each school's guidelines for each keyword and determined whether the word was being used in relation to crediting faculty for SMDS in the context of P&T procedures. The primary outcome measure was the dichotomous presence or absence of SMDS-specific keywords in each school's P&T guidelines. Results: The authors acquired P&T guidelines from 145/154 (94%) medical schools. After removing duplicate documents, the authors considered 139 guidelines. The keyword bank included 59 terms, of which 49 were specific to SMDS and 10 were umbrella terms that could be inclusive of SMDS. Of the 139 guidelines, 121 (87%) contained at least 1 SMDS-specific keyword. Schools had a median of 3 SMDS-specific keywords in their P&T guidelines. Conclusions: As the presence and impact of SMDS increase, schools should provide guidance on its role in the P&T process. Faculty should receive clear guidance on how to document quality SMDS for their promotion file. Abstract : Supplemental Digital Content is available in the text.